Suppressed vascular Rho-kinase activation is a protective cardiovascular mechanism in obese female mice - Barbosa, Gabriela S. [UNESP]; Costa, Rafael Menezes; Awata, Wanessa M.C.; Singh, Shubhnita; Alves, Juliano V.; Bruder-Nascimento, Ariane; Corrêa, Camila Renata [UNESP]; Bruder-Nascimento, Thiago (Portland Press, 2023)
Background: Obesity is the number one cardiovascular risk factor for both men and women and is a complex condition. Although a sex dimorphism on vascular function has already been noted, the underlying processes remain unclear. The Rho-kinase pathway has a unique role in controlling vascular tone, and in obese male mice, hyperactivation of this system results in worsened vascular constriction. We investigated whether female mice exhibit decreased Rho-kinase activation as a protective mechanism in obesity. Methods: We exposed male and female mice to a high-fat diet (HFD) for 14 weeks. At the end, energy expenditure, glucose tolerance, adipose tissue inflammation, and vascular function were investigated. Results: Male mice were more sensitive to HFD-induced body weight gain, glucose tolerance, and inflammation than female mice. After establishing obesity, female mice demonstrated increase in energy expenditure, characterized by an increase in heat, whereas male mice did not. Interestingly, obese female mice, but not male, displayed attenuated vascular contractility to different agonists, such difference was blunted by inhibition of Rho-kinase, which was accompanied by a suppressed Rho-kinase activation, measured by Western blot. Finally, aortae from obese male mice displayed an exacerbated inflammation, whereas obese female demonstrated a mild vascular inflammation. Conclusion: In obesity, female mice demonstrate a vascular protective mechanis m—suppression of vascular Rho-kinase—to minimize the cardiovascular risk associated with obesity, whereas male mice do not generate any adaptive response. Future investigations can help to understand how Rho-kinase becomes suppressed in female during obesity.